Proceeding of the conference quantum probability and infinite dimensional analysis : (World Scientific, 2003)
Contents: This volume consists of 18 research papers reflecting the impressive progress made in the field. It includes new results on quantum stochastic integration, quantum Markov processes, the stochastic limit, quantum teleportation and other areas.